Promoting permanent employment: Lessons from Spain - Ildefonso Mendez (SERIEs - Journal of the Spanish Economic Association, 2013)
This paper analyzes whether the two major labor market reforms implemented in Spain in the 1990s to reduce the share of temporary employment succeed in promoting flows into permanent employment. The 1994 reform severely restricted temporary contracts and the 1997 reform introduced a new permanent contract figure with lower payroll taxes and dismissal costs than the ordinary. To evaluate these non-targeted treatments I present an estimation procedure that uses pre-treatment outcomes to predict the one thatwould have been otherwise observed in the post-treatment period in the absence of the treatment and I derive its large sample properties. Using data from the Spanish Labor Force Survey I find that both reforms failed at reducing the share of temporary employment because they had no impact on contract conversions, which account for most new permanent contracts. The 1997 reform succeed in increasing permanent hirings for some groups of workers. My findings suggest that Spanish employers took advantage of wage and dismissal cost reductions to substitute permanent contracts for otherwise temporary ones.
Keywords: J32; J38; J65; 330; permanent employment; dismissal costs; payroll taxes; inverse probability weighted estimation; semiparametric methods